ANALISIS SWOT : Faktor Internal dan Eksternal dalam Upaya Meningkatkan Kualitas Pendidikan di MI Miftahul Ulum Beru - Rohmah, Afwatun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
ABSTRACT SWOT analysis is generally carried out to determine policies within an institution, organization. The main objective of this research is to be able to perform a SWOT analysis of internal and external factors at MI Miftahul Ulum Beru as an effort to improve the quality of education in schools. The method used in this research is descriptive qualitative with primary data sources from interviews, and secondary observations from documentation. The data analysis stage uses the Miles and Huberman data analysis stage, namely data reduction, data presentation and drawing conclusions. The stages of the research are pre-field, field and data analysis. The results of this research are SWOT analysis is carried out to understand and know the phenomena experienced by the school so that it can be handled in an appropriate way by the parties concerned. Things that need to be considered in the SWOT analysis carried out by researchers are the strategies that will be carried out to improve the quality of education at MI Miftahul Ulum Beru, including: conducting training and gradual development; cross-sectoral approaches and cooperation; and form creative innovations that are constructive and fun for children.